Capacity Building Forum Kesehatan Kelurahan (FKK) Dalam Mendukung Adaptasi Kebiasaan Baru Dalam Keluarga Di Kecamatan Tembalang - Putri Asmita Wigati; Ayun Sriatmi; Antono Suryoputro; Chriswardani Suryawati; Wulan Kusumastuti (Journal of Community Development, 2022)
To prevent and control the COVID-19 pandemic, the government establishes a policy of new normal adaptation by implementing health protocols in daily life. However, the community should be active in implementing new normal adaptation. Forum Kesehatan Kelurahan (FKK) as a forum for community participation in the health sector has an important role in the success of supporting health programs at the village level. Based on research studies, the application of new normal adaptation in Tembalang District by the community hasn’t been optimal. Therefore, the role of FKK in Tembalang District has to adapt new normal from the family. The ability and knowledge of FKK cadres regarding adaptation of new normal must be good in order to have sufficient capacity to support new normal families in Tembalang District. In this case, the capacity building of the FKK carried out through activities to 38 FKK cadres representing each sub-district in Tembalang District. Counseling done by doing pre-test, presenting materials, discussions with participants, and ended by post-test. The results of discussion, the community had made efforts to support the implementation of the new normal, there are education, field operations, reporting of COVID-19 cases, and jogo tonggo. Challenges for FKK are community’s lack awareness of COVID-19 pandemic and health protocols impportance. Post-test result showed increasing number of cadre with good knowledge about New Normal. In this activity, participants were also given a booklet. The capacity of FKK cadres to mobilize community will be stronger that hopefully can contribute more efforts to support the adaptation of new normal in the family and be able to solve challenges well.